Spectral Analysis of the Isolated Vowels of the Akmenė Dialect - Murinienė, Lina (Kalbotyra, 1998)
The article presents a spectral description of the isolated vowels of the Eastern Telšiai (Akmenė) dialect. It is suggested that in delimitating the front vowels the second formant is the more important and regarding the articulation or the vowels more important is the horizontal direction of movement of the tongue. In other words, a more important role is played by the height (the rising point) of the tongue: the Akmenė [ẹ], compared with [i], is retracted towards the middle region of the mouth. As for back vowels, labialized ones in particular, more important is the first formant, and regarding the articulation more important is the vertical movement of the tongue and the degree of the openness of the mouth. The Akmenė isolated vowels are compared with D. Jones’ cardinal vowels. It is concluded that by their spectral features the Akmenė vowels are more similar to the secondary rather than to primary cardinal vowels. Neither the extreme front nor the extreme back articulation is characteristic of the said vowels. Moreover, in articulating the vowels the activity of the lips is only slightly controlled: the front Akmenė vowels are much closer to the secondary front (i.e. labialized) cardinal vowels, the back vowels (except [a.], [a]) are similar to the secondary back (i.e. non-labialized) vowels. The common diagram of Akmenė and D. Jones’ cardinal vowels indicates that the trapezium of the Akmenė dialect vowels forms inside the trapezium of the cardinal primary vowels: the vowels being investigated are concentrated in the central area of the spectrum. It supports the view that the Akmenė dialect avoids extreme articulation, not only of the marked front or back but also of the upper and lower vowels. All this points to the inertness or the lips, which are not much controlled indeed. This is particularly true of the mid vowels [ẹ.], [ẹ], [ọ.], and [ọ].